Branding for the public sector : creating, building and managing brands people will value - Temporal, Paul (Chichester, West Sussex : Wiley, 2015)
"From government programs to non-profit organisations to global NGOs, organisations in the public sector are increasingly turning to branding strategies employed by for-profit companies to develop their images. Image is everything, particularly in the developing world in which many public-sector groups operate. Consequently, the public sector is the next big growth area in branding, but few books address branding strategy specific for this sector. Branding for the Public Sector fills this gap with powerful and effective branding strategies backed by case studies and examples. Author Paul Temporal covers branding architecture, brand vision, market research, brand perception, brand engagement, brand communication, managing brand change, and much more. Additionally, he covers the future of public sector branding and how organisations in the public sector may be a key driver of economic growth and prosperity through the twenty-first century. Branding for the Public Sector offers expert guidance for managers and leaders who want to build powerful, influential brands in the public sector"--
The public sector and branding -- Public sector brand categories -- The nation brand effect and brand architecture -- Building a power public sector brand : visions, values, emotions and personalities -- Brand positioning -- Public sector brand management -- Brand communications strategy -- Brand engagement -- Tracking brand success -- The future of public sector branding.
Includes index.
Print version record.
Keywords: Government marketing; Government publicity; Public relations and politics; Branding (Marketing); Branding (Marketing); Government marketing; Government publicity; Public relations and politics; Electronic books